Are they in or out? Exploring pre-service teachers’ knowledge, perceptions, and experiences regarding artificial intelligence (AI) in teaching and learning - Dayagbil, Filomena T.; Boholano, Helen B.; Sumalinog, Gino G. (Frontiers in Education, 2025)
IntroductionArtificial Intelligence (AI) continues to revolutionize the teaching and learning process. This study aimed to gather data on pre-service teachers’ perceived knowledge, perceptions, and experiences in utilizing AI in education, such as ChatGPT, Quillbot, and Grammarly.MethodsThis mixed-method study involved 515 participants from state universities in Central Visayas, Philippines, selected via stratified random sampling. Quantitative data were collected through a survey, while qualitative insights were gathered from focus group discussions and analyzed using thematic analysis.Results and discussionResults showed that pre-service teachers’ perceptions of AI revealed cautious optimism, with concerns about its limitations in handling complex tasks, bias, lack of originality, and the need for human oversight. They also recognized issues of factual inaccuracies, reliance on outdated data, and lack of contextual understanding, indicating a need for further education on AI’s ethical and practical use. Four themes emerged from the qualitative data: the role of AI in teaching and learning; challenges and ethical implications; capacity training for AI integration; and the link between AI tools and critical thinking.ConclusionIn conclusion, pre-service teachers recognize AI’s limitations and emphasize the importance of training for its responsible and effective use.RecommendationIt is recommended that AI use be integrated into the teacher education curriculum to prepare teachers for ethical and meaningful application in classrooms.